The Phenomenon of “Tao-for-Buddhism” in Dunhuang Taoist Manuscripts - Zhang, Peng (Religions, 2025)
The text Poxie lun:Daojing shijingfo wen破邪論:道經師敬佛文 (Treatise on Refuting Heresies: On the Respect of Taoist Scriptures for Buddha) records twenty-three items of “miscellaneous ancient records in Taoist scriptures” 道教古經古事雜抄. Half of these entries align with contents found in Dunhuang manuscripts and pertain to the practice of “replacing Buddhism with Taoism”. The Dunhuang manuscripts that involve the content of “replacing Buddhism with Taoism” can be categorized into five situations: First, Taoist scriptures that retain Buddhist terminology which was later replaced by later generations; Second, instances where traces of Buddhist terminology remain, showing signs of having been altered or replaced; Third, cases where the replacement of Buddhist terminology has already been completed in the manuscripts; Fourth, instances where, after replacing Buddhist terminology, the sentence structure was also revised; Fifth, sections that were preserved which, in later generations, were deleted due to their content relating to the blending of Buddhism and Taoism. These instances of “replacing Buddhism with Taoism” may reflect efforts by Taoism to remove Buddhist elements amid criticism or an attempt by Buddhist monks to preserve Buddhism’s sanctity by altering Taoist texts. The Dunhuang Taoist manuscripts offer vibrant historical material for discussing interactions between Buddhism and Taoism in medieval China.